HUBUNGAN POLA MP-ASI TERHADAP STATUS GIZI ANAK DIPUSKESMAS SURADITA KAB.TANGERANG - Hanifah Eka Cahyaningsih (Fakultas Ilmu kesehatan UPN Veteran Jakarta, 2021)
Complementary feeding (MP-ASI) is given when the child is 6 months old, the function of MP-ASI itself is to supplement the nutritional needs of breast milk. WHO recommends giving good and nutritious MP-ASI, by categorizing it according to age, texture, number and frequency. This study aims to analyze the relationship of complementary feeding patterns (MP-ASI) with the nutritional status of children in the Suradita Community Health Center in Tangerang Regency. This study used a cross sectional design with 90 participants through a purposive sampling method. Data collection used questionnaire pattern of giving MP-ASI which has been tested for validity and reliability. Statistical test results with 95% confidence intervals indicate that a p-value of 0.007 means that there is a significant relationship between the pattern of giving MP-ASI and nutritional status with an odds ratio (OR) of 4.960 which means that children given with a correct MP-ASI pattern is 4,960 times have higher chance of having a normal nutritional status compared to children who are not given a correct MP-ASI pattern. Researcher suggest in subsequent studies to measure the energy consumed by children to be able to measure MP-ASI pattern more specific Researchers suggest in subsequent studies to measure also a lot of energy consumed by children, so that the measurement of the MP-ASI pattern becomes more specific.